(untitled) (International Journal of Engineering Sciences & Management Research, 2015)
The ternary homogeneous quadratic equation given by 2 2 2 (x  y )  xy  x  y 116z representing a cone is analyzed for its non-zero distinct integer solutions. A few interesting relations between the solutions and special polygonal and pyramided numbers are presented.